Derivatives of alkyl gallate triphenylphosphonium exhibit antitumor activity in a syngeneic murine model of mammary adenocarcinoma - Peredo-Silva, Liliana; Fuentes-Retamal, Sebastián; Sandoval-Acuña, Cristian; Pavani, Mario; Maya, Juan D; Castro-Castillo, Vicente; Madrid-Rojas, Matías; Rebolledo, Solange; Kemmerling, Ulrike; Parra, Eduardo; Ferreira, Jorge (Toxicology and applied pharmacology, 2017)
We previously demonstrated that alkyl gallates coupled to triphenylphosphine have a selective and efficient antiproliferative effect by inducing mitochondrial uncoupling in vitro due to the increased mitochondrial transmembrane potential of tumor cells. Therefore, in this work, the in vivo antitumor activities of alkyl gallate triphenylphosphonium derivatives (TPP+C8, TPP+C10 and TPP+C12) were evaluated in a syngeneic murine model of breast cancer. We found that TPP+C10 increased the cytosolic ADP/ATP ratio and significantly increased the AMP levels in a concentration-dependent manner in TA3/Ha murine mammary adenocarcinoma cells. Interestingly, TPP+C10 induced a decrease in the levels of cellular proliferation markers and promoted caspase-3 activation in tumor-bearing mice. Additionally, TPP+C10 inhibited tumor growth in the syngeneic mouse model. Importantly, 30days of intraperitoneal (i.p.) administration of the combination of TPP+C10 (10mg/kg/48h) and the antibiotic doxycycline (10mg/kg/24h) completely eliminated the subcutaneous tumor burden in mice (n=6), without any relapses at 60days post-treatment. This enhancement of the individual activities of TPP+C10 and doxycycline is due to the uncoupling of oxidative phosphorylation by TPP+C10 and the inhibition of mitochondrial biogenesis by doxycycline, as demonstrated by loss of mitochondrial mass and overexpression of PGC1-α as an adaptive response. Moreover, i.p. administration of TPP+C10 (10mg/kg/24h) to healthy mice did not produce toxicity or damage in organs important for drug metabolism and excretion, as indicated by hematological, biochemical and histological assessments. These findings suggest that the combination of TPP+C10 with doxycycline is a valuable candidate therapy for breast cancer management.
Keywords: apoptóza; tumor burden; Oxidative Phosphorylation; Alkyl gallate triphenylphosphonium derivatives; Cell Proliferation; Apoptosis; kyselina gallová; Cell Line, Tumor; doxycyklin; Antineoplastic Agents; Mammary Neoplasms, Experimental; Organophosphorus Compounds; Gallic Acid; Delocalized lipophilic cation; Signal Transduction; vztah mezi dávkou a účinkem léčiva; Doxycycline; protinádorové látky; oxidativní fosforylace; myši; Tumor Burden; adenosintrifosfát; protokoly protinádorové kombinované chemoterapie; Uncoupling of mitochondrial function; adenokarcinom; Mice; Dose-Response Relationship, Drug; proliferace buněk; signální transdukce; mitochondrie; biogeneze organel; Syngeneic murine model of breast cancer; Caspase 3; organofosforové sloučeniny; mužské pohlaví; Mitochondria; zvířata; kaspasa 3; Organelle Biogenesis; Time Factors; experimentální nádory mléčných žláz; Animals; nádorové buněčné linie; spotřeba kyslíku; časové faktory; Male; Adenocarcinoma; Adenosine Triphosphate; Antineoplastic Combined Chemotherapy Protocols; Oxygen Consumption